Asymptotic behaviour of certain families of harmonic bundles on Riemann surfaces - Mochizuki, Takuro (Journal of topology, 2016)
Let (E,∂¯E,θ) be a stable Higgs bundle of degree 0 on a compact connected Riemann surface. Once we fix a flat metric hdet(E) on the determinant of E, we have the harmonic metrics ht (t>0) for the stable Higgs bundles (E,∂¯E,tθ) such that det(ht)=hdet(E). We study the behaviour of ht when t goes to ∞. First, we show that the Hitchin equation is asymptotically decoupled under the assumption that the Higgs field is generically regular semisimple. We apply it to the study of the so‐called Hitchin Wentzel, Kramers, and Brillouin‐problem. Secondly, we study the convergence of the sequence (E,∂¯E,θ,ht) in the case rankE=2. We introduce a rule to determine the parabolic weights of a ‘limiting configuration’, and we show the convergence of the sequence to the limiting configuration in an appropriate sense. The results can be appropriately generalized in the context of Higgs bundles with a Hermitian–Einstein metric on curves.